The Arab Spring Five Years Later : Case Studies. - Ghanem, Hafez (Brookings Institution Press, 2016)
Volume 1 of The Arab Spring Five Years Later is based on extensive research conducted by scholars from a variety of backgrounds, including many associated with the Japan International Cooperation Agency (JICA). The original research papers are gathered in volume 2 and are available for readers who wish to go even further in understanding the economic background of the Arab Spring. Papers examine women's issues and agricultural practices in Morocco; urban transportation, small enterprises, governance, and inclusive planning in Egypt; reconstruction in Iraq; youth employment in Tunisia; education in Yemen; and more. In addition to Hafez Ghanem, contributors include Mongi Boughzala (University of Tunis ElManar, Tunisia), Mohamed Tlili Hamdi (University of Sfax, Tunisia), Yuriko Kameyama (JICA), Hideki Matsunaga (JICA), Mayada Magdy (JICA), Yuko Morikawa (JICA), Akira Murata (JICA), Kei Sakamoto (JICA), Seiki Tanaka (JICA), Masanori Yoshikawa (JICA), and Takako Yuki (JICA).